Elwyn Righetti - Betty Righetti Middlecamp::::::::: (1944)
Elwyn Righetti is San Luis Obispo's best-known war hero, although his fate is still unknown. A Cal Poly graduate and son of a long-time Edna Valley ranching family, Righetti joined the Army Air Corps in 1939 and served as an instructor before requesting overseas duty in 1944. Dubbed "Eager El" by admiring comrades in arms, Righetti commanded the 55th Fighter Group, Eighth Air Force. On his 30th birthday, April 17, 1945, he was shot down over Dresden - 21 days before the war ended. Fellow aviators saw Righetti climb out of his P-51 Mustang as a crowd of German civilians gathered. The fighter ace was never heard from again. His sister, Betty Righetti Middlecamp, still searches for information on her brother's fate. Righetti attained the rank of colonel and was awarded the Distinguished Service Cross, the Silver Star, two Distinguished Flying Crosses, and 22 Air Medals. Four generations of the Righetti-Middlecamp family have attended Cal Poly.